Early-Life Skin Microbiome Trajectories in Atopic Dermatitis and Food Allergy: A Systematic Review - Diah Lusi Fajar Agustina; Desy Sulistiyorini (Journal of Health Science and Medical Therapy, 2026)
Atopic dermatitis and food allergies are common conditions in early childhood and can be influenced by environmental factors in early life. The skin microbiome has been suggested as a factor in the development of atopic diseases, but longitudinal evidence to date remains limited. The objective of this study was to synthesize longitudinal observational evidence regarding the development of the skin microbiome in early life and its association with atopic dermatitis and food allergies. A systematic search was conducted in the PubMed and Scopus databases on November 21, 2025. The inclusion criteria for the literature review were longitudinal studies that took repeated skin microbiome samples from birth to 24 months of age and reported outcomes of atopic dermatitis and/or food allergies. Study selection, data extraction, and quality assessment using the Newcastle-Ottawa Scale were performed independently by two reviewers. Due to methodological heterogeneity, the study results were synthesized narratively. Screening of the full-text articles yielded five longitudinal studies that met the inclusion criteria. Skin microbiome development in early life differed between children who later developed atopic dermatitis and those who did not, mainly characterized by a decrease in microbial diversity, changes in commensal microbial colonization, and delayed microbiome maturation. Evidence linking skin microbiome development to food allergy outcomes is still limited and inconsistent. Skin microbiome development in early life differs between infants who later develop atopic dermatitis and those who do not, while evidence related to food allergies is still insufficient. Further standardized longitudinal studies are needed to clarify these relationships.